Perbandingan Hasil Pemeriksaan Leukosit dan Eritrosit Urin Menggunakan Urin Pagi dan Sewaktu Metode Carik Celup pada Penderita Infeksi Saluran Kemih - Jurnal syarif; Riska yanti (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
This research has a background of urinary tract infections in Indonesia, especially in South Sulawesi, so that the examination uses urine more often when, if the morning is used it will experience storage and allow changes in the composition of the urine and this can affect the results of the examination. In this study, the researcher wanted to find out whether there were differences in the results of leukocyte and erythrocyte examination using urine in the morning and during the strip-dip method in patients with urinary tract infections. The purpose of this study was to compare and determine the results of the examination of urinary leukocytes and erythrocytes using morning urine and the dipstick method in patients with urinary tract infections. This research is a laboratory research.The results of the study were analyzed using the statistical sign test which was carried out at the 95% confidence level. The rejection was 1.96 when compared to the value of z = 0.08 < tc = 1.96. In this case, there was no significant difference in the examination of leukocytes and erythrocytes in urine using morning urine. and from time to time the infection looks for a dye in patients with the urinary tract. Based on the results of the research above, it is recommended that morning urine can be used to examine urine leukocytes and erythrocytes at any time